A statistical intra-genre analysis of cross-national environmental news translation. (September 2018) - Ji, Meng
This study investigates the instrumental role of translated environmental news in informing public opinions on environmental issues among Chinese-speaking communities. Its contribution to methodology is exploring the automatic corpus annotation tools, that is, semantic analysis system. Its contribution to theory is identifying and distinguishing among three recurrent sub-news-types of translated environmental news published on BBC China, that is, governance; international relations and environmental science. Discourse features attributed to these subtypes of environmental news underscore BBC China's reporting styles and strategies and largely explain its wide appeal and credibility among the target audiences.